2014
DOI: 10.1155/2014/853086
|View full text |Cite
|
Sign up to set email alerts
|

A RXR Ligand 6-OH-11-O-Hydroxyphenanthrene with Antitumour Properties Enhances (−)-Epigallocatechin-3-gallate Activity in Three Human Breast Carcinoma Cell Lines

Abstract: (−)-Epigallocatechin-3-gallate (EGCG) and chemotherapeutic agents cotreatment can improve cytotoxicity against cancer cells. We showed that EGCG and the rexinoid 6-OH-11-O-hydroxyphenanthrene (IIF), given together, were cytotoxic toward MCF-7, MCF-7TAM, and MDA-MB-231, three breast carcinoma cell lines showing different molecular characteristics. Cell growth arrest and apoptosis were greater after EGCG and IIF cotreatment than after individual administration. Cytotoxicity was related to upregulation of 67-kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…MCF-7 cells resistant to tamoxifen (MCF-7TAM) were selected by growing MCF-7 cells in MEM medium without Phenol Red, containing 2 mM L-glutamine, 50 U/ml penicillin, 50 μg/ml streptomycin, 10 % FBS serum charcoal treated and 10 −7 M 4-OH-hydroxytamoxifen as previously described 17 [17]. In order to avoid any risk of contamination, the cell lines were assayed for oestrogen receptor α (ERα) expression by reverse transcription-PCR (RT-PCR) and immunoflurescence every 3 months: MCF-7 expressed ERα to a great extent, whereas MDA-MB-231 was completely devoid of ERα expression.…”
Section: Methodsmentioning
confidence: 99%
“…MCF-7 cells resistant to tamoxifen (MCF-7TAM) were selected by growing MCF-7 cells in MEM medium without Phenol Red, containing 2 mM L-glutamine, 50 U/ml penicillin, 50 μg/ml streptomycin, 10 % FBS serum charcoal treated and 10 −7 M 4-OH-hydroxytamoxifen as previously described 17 [17]. In order to avoid any risk of contamination, the cell lines were assayed for oestrogen receptor α (ERα) expression by reverse transcription-PCR (RT-PCR) and immunoflurescence every 3 months: MCF-7 expressed ERα to a great extent, whereas MDA-MB-231 was completely devoid of ERα expression.…”
Section: Methodsmentioning
confidence: 99%
“…We found that RARα protein expression nearly doubled in EGCG+IIF-treated samples ( Figure 1 B). RXR and particularly RXRγ are the main targets of IIF: as we found that RXRγ mRNA was hardly detectable (data not shown), we used a primer couple that is able to cover a homology region in RXRβ and γ genes, a strategy that we already applied elsewhere [ 12 ]. As expected, RXRα and βγ RNA expression augmented after IIF treatment and RXRγ protein expression increased significantly after all treatments ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were seeded and after 18 h were placed in serum-free medium (D-MEM) with EGCG or IIF or both for 24 h. MMP2 and MMP9 activity was determined by gelatine zymography, as previously described [ 12 ]. The MMP activities, indicated by clear bands of gelatin digestion on a blue background, were quantified by using densitometric image analysis software (Image Lab Master, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we demonstrated that the combination of IIF and EGCG had a higher activity than the individual administration. IIF and EGCG can have a common signaling pathway that induces apoptosis by reducing epidermal growth factor receptor activation and its downstream kinase AKT-1 [75] .…”
Section: The New Rexinoid Iif Can Kill Bcscsmentioning
confidence: 99%